Evaluación de confiabilidad con alta penetración de fuentes de energía renovable no convencionales (2020)
This project consists of developing a program in MATPOWER that allows for a reliability evaluation in power systems when there is penetration of non-conventional renewable energies (solar and/or wind). In this tool, the point estimate method was used as a probabilistic analysis methodology where each renewable energy source is modeled according to its capacity and its first 4 central moments. The methodology used consists of evaluating 2m+1 evaluation cases, m the number of wind farms and solar farms installed in the system, each case with its respective location (power generated by the farms) and its respective weight in the total analysis. Taking the value of the power generated by each non-conventional renewable energy source, the reliability indices LOLP, EENS, frequency, LOLE and interruption costs for the system operating under the conditions given by each evaluation case were calculated and the mean and standard deviation of each reliability index was calculated...